2013
DOI: 10.1186/1471-2458-13-772
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption, smoking and overweight as a burden for health care services utilization: a cross-sectional study in Estonia

Abstract: BackgroundAlcohol consumption, smoking and weight problems are common risk factors for different health problems. We examine how these risk factors are associated with the use of health care services.MethodsData for 6500 individuals in the 25–64 age group came from three cross-sectional postal surveys conducted in 2004, 2006, and 2008 in Estonia. The effect of alcohol consumption, smoking and weight problems on the use of primary and specialist care services, hospitalizations and ambulance calls was analysed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
4
23
1
6
Order By: Relevance
“…Анализ потребления ресурсов системы здравоохранения и ВН позволил исследовать ассоциации обращений за медицинской помощью и ВН в течение [5,22]. Потребление табака статистически значимо увеличивает вероятность обращения за всеми видами медицинской помощи и наступления ВН в нашем исследовании, кроме вероятности госпитализации женщин, а также значимо повышает частоту амбулаторных обращений женщин к врачу, то же самое продемонстрировали крупные исследования в Германии и Эстонии [3,23].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Анализ потребления ресурсов системы здравоохранения и ВН позволил исследовать ассоциации обращений за медицинской помощью и ВН в течение [5,22]. Потребление табака статистически значимо увеличивает вероятность обращения за всеми видами медицинской помощи и наступления ВН в нашем исследовании, кроме вероятности госпитализации женщин, а также значимо повышает частоту амбулаторных обращений женщин к врачу, то же самое продемонстрировали крупные исследования в Германии и Эстонии [3,23].…”
Section: Discussionunclassified
“…Ожирение среди женщин -один из самых ресурсоемких ФР, вносящий значимый вклад в повышенное использование всех видов медицинской помощи и также увеличивает вероятность наступления ВН и частоту вызовов СМП, в то время как мужчинам с ожирением с большей вероятностью потребуется стационарная помощь, и значимо возрастает число случаев ВН. Распространение ожирения способствуют увеличению нагрузки на систему здравоохранения, что подтверждается результатами крупных исследований [23,25,26].…”
Section: Discussionunclassified
“…U kanadskoj studiji, takođe, pušači rjeđe koriste usluge zdravstvene zaštite u odnosu na nepušače [21], dok je u estonskoj studiji pušen-je značajno povezano sa korišćenjem usluga primarne zdravstvene zaštite [22].…”
Section: Diskusijaunclassified
“…Za razliku od pušača, gojazne osobe u našoj studiji koriste dva puta češće usluge doktora porodične medicine u odnosu na normalno uhranjene, što je u skladu sa rezultatima estonske studije [22].…”
Section: Diskusijaunclassified
“…Several studies have revealed that increased morbidity and mortality attributed to BRFs are associated with the use of health services and increased healthcare costs (Anderson et al 2005;Bertakis and Azari 2006;Hill et al 2009;Sturm 2002;Vals et al 2013). Hill and colleagues estimated that in the period 2004-06, the average medical annual costs were greater among Americans with one or more BRFs ($4,432), compared with those with no BRFs ($2,382), and increased with age (Hill et al 2009).…”
Section: Introductionmentioning
confidence: 99%